The Effect of Selection and Training on Employee Performance of Ptpn Iii Giting Nest Gardens - Prayuda, Indra; Lidia Yunita (SEAN Institute, 2022)
This study aims to determine the effect of selection and training on the performance of employees of PTPN III Kebun Sarng Giting. The population in this study were 125 employees of PTPN III Kebun Sarang Giting and the sample was taken using probability sampling with disproportinate stratified random sampling technique so that the total sample was 56 people. The data were obtained by distributing questionnaires to respondents and then the data were processed using SPSS version 24.0 for windows. The data analysis technique used is multiple linear regression test with the formula Y = a + bX1 + bX2 + e. The simple linear regression test results obtained by the equation Y = 11,270 + 0.121 X1 + 0.386 X2 + e, where selection and training have a positive effect on performance variables. the t value obtained by the selection variable (X1) is 2.580 and training (X2) is 2.025 where the t value is greater than the t table value which is 2.004. The table above also shows a sig value of 0.00 where the significance value is smaller than 0.05. So it can be concluded that selection (X1) and training (X2) have a significant effect on performance (Y). The result of the F test is 5,176 with a sig level of 0,000, therefore the sig value of 0,000> 0.05 and the value of F count> F table, namely 5,176> 4,020, this indicates that the independent variables X1 and X2 simultaneously have a positive and significant effect on the dependent variable. Y. The value of R20,676 means that 67.6% of employee performance (Y) can be affected by the selection (X1) and training (X2) variables. While the remaining 32.4% is influenced by other variables not included in this study.